Benchmarking as a tool for improving the competitiveness of an economic university ("Journal "U". Economy. Management. Finance.", 2025)
The article explores the potential of benchmarking as a systemic tool for ensuring and improving the quality of educational activities in a modern Russian university. Using the example of Rostov State University of Economics (RINH), the article analyzes the theoretical background and practical aspects of integrating benchmarking into the management system. The author has developed a multi-level implementation model that covers the institutional, functional, operational, and evaluation levels. Special attention is given to adapting best practices to the regional socio-economic conditions of the Rostov Region. The article presents the criteria and indicators of benchmarking system effectiveness, as well as the stages of its practical implementation. The study is based on the analysis of modern scientific publications, strategic documents on the development of education and regional policy.
Keywords: benchmarking; quality of education; university management system; Rostov State University of Economics